Linking dietary patterns with gut microbial composition and function. (4th March 2017) - Sheflin, Amy M.; Melby, Christopher L.; Carbonero, Franck; Weir, Tiffany L.
ABSTRACT: Emerging insights have implicated the gut microbiota as an important factor in the maintenance of human health. Although nutrition research has focused on how direct interactions between dietary components and host systems influence human health, it is becoming increasingly important to consider nutrient effects on the gut microbiome for a more complete picture. Understanding nutrient-host-microbiome interactions promises to reveal novel mechanisms of disease etiology and progression, offers new disease prevention strategies and therapeutic possibilities, and may mandate alternative criteria to evaluate the safety of food ingredients. Here we review the current literature on diet effects on the microbiome and the generation of microbial metabolites of dietary constituents that may influence human health. We conclude with a discussion of the relevance of these studies to nutrition and public health and summarize further research needs required to realize the potential of exploiting diet-microbiota interactions for improved health.